2022
DOI: 10.1039/d2cs00014h
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-intercalating conjugated oligoelectrolytes

Abstract: Membrane-intercalating conjugated oligoelectrolytes are emerging as versatile tools to modify or functionalize lipid bilayers. Through modular chemical design, this new molecular platform has applications in a range of biological fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…Conjugated oligoelectrolytes (COEs) are a class of molecules comprising a hydrophobic conjugated backbone decorated by pendant ionic functional groups (1)(2)(3). Membrane-intercalating COEs are based on a linear topology and mimic the general spatial distribution of hydrophilic and hydrophobic domains of lipid bilayers (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conjugated oligoelectrolytes (COEs) are a class of molecules comprising a hydrophobic conjugated backbone decorated by pendant ionic functional groups (1)(2)(3). Membrane-intercalating COEs are based on a linear topology and mimic the general spatial distribution of hydrophilic and hydrophobic domains of lipid bilayers (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Department of Chemistry, National University of Singapore, Singapore 117543, Singapore 2. Institute of Polymer Optoelectronic Materials and Devices, State Key Laboratory of Luminescent Materials and Devices, South China University of Technology, Guangzhou 510640, PR China 3. Institute for Functional Intelligent Materials, National University of Singapore, Singapore 117544, Singapore 4.…”
mentioning
confidence: 99%
“…Among them, the inorganic contrast agents still require substantial efforts to achieve practical clinical use, due to their biodegradability difficulties and potential chronic toxicity issues deriving from the long-term retention in vivo, and the biocompatibility problems (e.g., potential immunoreactions). By comparison, organic contrast agents, allowing not only good biocompatibility but also flexibility in the structure modification, , are promising alternatives to address the challenges encountered in their inorganic counterparts. While among the organic contrast agents, the SPs demonstrate higher photostability than small molecules .…”
Section: Introductionmentioning
confidence: 99%
“…These issues drive the researchers to develop cost-effective polymers for large-scale production. Alternatively, the thiophene-based polymers, which have the advantages of abundant raw materials, simple chemical structure and synthesis, and easy realization of large-scale production, , are more competitive and promising for commercialization. Moreover, it has been reported that the oligo­(ethylene glycol) chains, when used as the side chains, endow the resulting SPs with good biocompatibility in tissues and high processability in polar solvents due to their polarity and hydrophilicity .…”
Section: Introductionmentioning
confidence: 99%
“…[7] Of particular relevance is a class of watersoluble and membrane-intercalating molecules called conjugated oligoelectrolytes (COEs), which are characterized by a conjugated core with ionic pendant groups. [8] Previous reports primarily employ oligo p-phenylenevinylene (OPV)-based COEs to amplify transmembrane electron transport. [9] Initial studies suggested that OPV-COEs act as "molecular wires" by facilitating electron tunneling or hopping through their conjugated backbones.…”
mentioning
confidence: 99%